User feedback practices in continuous software engineering - Johanßen, Jan Ole; Kleebaum, Anja; Bruegge, Bernd; Paech, Barbara (Software Engineering 2020, 2020)
We summarize the paper "How do practitioners capture and utilize user feedback during continuous software engineering?", which was presented at the 2019 edition of the IEEE International Requirements Engineering Conference (RE) in Jeju Island, South Korea.